Locating mammalian transcription factor binding sites: A survey of computational and experimental techniques - Elnitski, Laura; Jin, Victor X.; Farnham, Peggy J.; Jones, Steven J.M. (Genome Research, 2006)
Fields such as genomics and systems biology are built on the synergism between computational and experimental techniques. This type of synergism is especially important in accomplishing goals like identifying all functional transcription factor binding sites in vertebrate genomes. Precise detection of these elements is a prerequisite to deciphering the complex regulatory networks that direct tissue specific and lineage specific patterns of gene expression. This review summarizes approaches for in silico, in vitro, and in vivo identification of transcription factor binding sites. A variety of techniques useful for localized- and high-throughput analyses are discussed here, with emphasis on aspects of data generation and verification.
10.1101/gr.4140006